Deep learning for internet of things infrastructure - Ghosh, Uttam; Alazab, Mamoun; Bashir, Ali Kashif; Pathan, Al-Sakib Khan (CRC Press, Taylor & Francis Group, 2022)
This book promotes and facilitates exchanges of research knowledge and findings across different disciplines on the design and investigation of deep learning (DL)–based data analytics of IoT (Internet of Things) infrastructures. Deep Learning for Internet of Things Infrastructure addresses emerging trends and issues on IoT systems and services across various application domains. The book investigates the challenges posed by the implementation of deep learning on IoT networking models and services. It provides fundamental theory, model, and methodology in interpreting, aggregating, processing, and analyzing data for intelligent DL-enabled IoT.
1. Data Caching at Fog Nodes under IoT Networks: Review of Machine Learning Approaches; Riya, Nitin Gupta, and Qin Xin; 2. ECC-Based Privacy-Preserving Mechanisms Using Deep Learning for Industrial IoT: A State-of-the-Art Approaches; R. Sivaranjani, P. Muralidhara Rao, and P. Saraswathi; 3. Contemporary Developments and Technologies in Deep Learning–Based IoT; Prishita Ray, Rajesh Kaluri, Thippa Reddy G., Praveen Kumar Reddy M., and Kuruva Lakshmanna; 4. Deep Learning–Assisted Vehicle Counting for Intersection and Traffic Management in Smart Cities; Guy M. Lingani, Danda B. Rawat, and Moses Garuba; 5. Toward Rapid Development and Deployment of Machine Learning Pipelines across Cloud-Edge; Anirban Bhattacharjee, Yogesh Barve, Shweta Khare, Shunxing Bao, Zhuangwei Kang, Aniruddha Gokhale, and Thomas Damiano; 6. Category Identification Technique by a Semantic Feature Generation Algorithm; Somenath Chakraborty; 7. Role of Deep Learning Algorithms in Securing Internet of Things Applications; Rajakumar Arul, Shakila Basheer, Asad Abbas, and Ali Kashif Bashir; 8. Deep Learning and IoT in Ophthalmology; Md Enamul Haque and Suzann Pershing; 9. Deep Learning in IoT-Based Healthcare Applications; S.M. Zobaed, Mehedi Hassan, Muhammad Usama Islam, and Md Enamul Haque; 10. Authentication and Access Control for IoT Devices and Its Applications; Ananda Kumar S., Arthi B., Aruna M., Aaisha Makkar, and Uttam Ghosh; 11. Deep Neural Network–Based Security Model for IoT Device Network; Dukka Karun Kumar Reddy, Janmenjoy Nayak, Bighnaraj Naik, and G. M. Sai Pratyusha